On Safe Space in Education: A Polish-Vietnamese Comparative Study - Dorota Domalewska (Librelloph, 2021)
Safe space describes a classroom climate that feels secure, supportive, and risk-free so that students can honestly express their individuality and opinions without fear of being the target of violence harassment, or hate speech. In this paper, we examine the relationship between the school environment, individual characteristics and family in shaping students’ perceptions of safe learning environment. The Safe Learning Environment Survey was designed and distributed to a convenience sample of 360 undergraduate students at universities in Poland and Vietnam. Results reveal that neither sex nor family context affect students’ feeling of safety at school. However, there is a high association with nationality in feeling safe at school. Polish and Vietnamese students differ in their opinions why safe space should be enhanced as well as what the teacher and peers’ roles are in shaping safe atmospheres. These findings have significant implications for multicultural classes: understanding the factors that enhance school safety will help to form the collaborative and inclusive environment where students’ performance improves.